2015
DOI: 10.1093/jhered/esv005
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Genetic Structure and Diversity ofGalaxias maculatus(Jenyns, 1848) Along the Chilean Coast: Stock Identification for Fishery Management

Abstract: Galaxias maculatus (Pisces: Galaxiidae) commonly known as "puye" has a disjunct distribution along the Southern Hemisphere including landlocked and migratory populations at latitudes over 30°S in South America, Australia, Tasmania, and New Zealand. Chilean artisanal fishery of G. maculatus has become less important as a resource due to multiple factors including overexploitation, pollution, introduction of predators, and competitors. At the same time, the current conservation status of the species in Chile is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…habitat preferences, reproductive mode and bathymetric range). A concordance between historic biogeographic and contemporary phylogeographic patterns supports that evolutionary forces determining species distributions are also associated with spatial patterns of populations genetic structure 5,6,18,44,45 . Here we corroborate previous molecular results in the species 24,28 , and enhance our understanding of the Quaternary biogeography of the species by recognizing two clearly discriminated genetic clusters currently found in: 1) temperate areas across the Chile-Peru province, north of the 42°S in the Pacific, and 2) cold and temperate areas across the Magellan and Argentina provinces, respectively.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…habitat preferences, reproductive mode and bathymetric range). A concordance between historic biogeographic and contemporary phylogeographic patterns supports that evolutionary forces determining species distributions are also associated with spatial patterns of populations genetic structure 5,6,18,44,45 . Here we corroborate previous molecular results in the species 24,28 , and enhance our understanding of the Quaternary biogeography of the species by recognizing two clearly discriminated genetic clusters currently found in: 1) temperate areas across the Chile-Peru province, north of the 42°S in the Pacific, and 2) cold and temperate areas across the Magellan and Argentina provinces, respectively.…”
Section: Discussionmentioning
confidence: 70%
“…This break represents the southern limit for many Chile-Peru Province species and the northern border for numerous Magellan ones 13,36 . The shift in species composition recorded in marine organisms at 42°S in the southeast Pacific has been explained by changes in salinity and wave exposure 48,51 , topographical shifts of the coastline as a consequence of the increased number of fjords and channels 10,11,47 , differences in main oceanographic patterns 13,18,19,36,50 , and Quaternary glaciological histories 18,19,27,43 . In fact, this biogeographic limit coincides with the separation of the West Wind Drift into two main Pacific currents, the Humboldt Current System flowing north across the Central Chilean coast and the Cape Horn Current heading south along the Pacific Magellan margin 36,46 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, microsatellite markers revealed that G. maculatus populations from northern Patagonia exhibit higher genetic diversity and are more highly differentiated (within watersheds) that G. maculatus populations from Southern Patagonia, a pattern explained by the lesser effects of glaciations in northern than in southern Patagonia [6]. West of the Andes in Chile, DNA sequence diversity patterns indicate that estuarine G. maculatus exhibit relatively low genetic differentiation over 1500 Km of coastal waters south of 42 • S, where the glaciers reached the sea during the LGM, a pattern that contrasts with G. maculatus populations north of 42 • S [35,[44][45][46].…”
Section: Galaxias Maculatusmentioning
confidence: 95%
“…Accordingly, a marked decline in genetic diversity through bottleneck processes or founder effects followed by population expansion is expected [103]. Evidence of such demographic processes has been recorded in several Patagonian near-shore marine species [20,24,25,34,111116,125,126]. In contrast, little evidence of LGM ice apart from the small cirques and short (max.…”
Section: Discussionmentioning
confidence: 99%